2007
DOI: 10.1007/s11547-007-0121-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional study of the transplanted kidney with power Doppler US and time/intensity curves

Abstract: Data showed significant variations according to renal graft function (no abnormality, acute tubular necrosis or chronic rejection). Although confirmation by a larger series is required, our findings appear to indicate pathognomonic patterns in patients with chronic rejection and acute tubular necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…The mean ± SD of resistive index(RI) was 0.63 ± 0.06 in normal group, 0.76 ± 0.03 in ATI group, and 0.66 ± 0.05 in CAI group; these results matched with the study done by Farina et al (2007) [19] who studied 3 groups: (A) patient without disease, (B) patient with chronic rejection, and (C) patient with acute tubular necrosis; the range of RI for the Group A was 0.6-0.72, the Group B was 0.69-.79, and the group C was 0.68-78. On the other hand, our results disagreed with Ozkan et al (2013) [10] who reported that there was no significant correlation between renal parenchymal stiffness and RI in his population, and this is maybe due to the smaller studied group with ATI in his study.…”
Section: Discussionsupporting
confidence: 80%
“…The mean ± SD of resistive index(RI) was 0.63 ± 0.06 in normal group, 0.76 ± 0.03 in ATI group, and 0.66 ± 0.05 in CAI group; these results matched with the study done by Farina et al (2007) [19] who studied 3 groups: (A) patient without disease, (B) patient with chronic rejection, and (C) patient with acute tubular necrosis; the range of RI for the Group A was 0.6-0.72, the Group B was 0.69-.79, and the group C was 0.68-78. On the other hand, our results disagreed with Ozkan et al (2013) [10] who reported that there was no significant correlation between renal parenchymal stiffness and RI in his population, and this is maybe due to the smaller studied group with ATI in his study.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, CEUS can analyse renal blood flow quantitatively [43]. Through analyzing the echo volume and changes in the contrast agent microbubbles in the ROI over time to generate the TIC, quantitative parameters obtained from the TIC can be used to objectively and accurately quantify renal cortical haemodynamic changes [44]. The study by Dong et al [45] showed that renal function changes in patients with DN can be monitored by changes in the TIC curve parameters of the renal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…US contrast agents (USCAs) nowadays in use are safe in patients with renal diseases [6] and have been used for functional evaluation of the transplanted kidney [7,8]. CEUS (contrast-enhanced ultrasonography) performed with Sonazoid (Sonazoid™, Daiichi-Sankyo, Tokyo) as contrast medium has been tested on patients with chronic renal failure, showing that USCA enhancement decreases with the severity of renal function impairment [9].…”
Section: Introductionmentioning
confidence: 99%